Local Wisdom-Based Marketing Communication at the Tofu Factory in Sana Daja Village - Desi Endang Maisuri; Faridatul Jannah; Fitri Inayah (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
This study aims to analyze the forms and implementation of local wisdom-based marketing communications at a tofu factory in Sana Daja Village. Facing the development of the modern market, businesses in this village strive to maintain local cultural values ​​such as mutual cooperation (gotong royong), honesty, simplicity, and friendliness as the main foundations for interacting with consumers. The research method used was descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. The results indicate that local wisdom values ​​play a crucial role in developing effective and sustainable marketing strategies. The value of mutual cooperation is reflected in the cooperation between producers and the surrounding community, while honesty and friendliness are key to building consumer trust and loyalty. Furthermore, businesses are able to adapt to changes in the modern market through the use of social media, without abandoning the local character that defines their businesses. Overall, local wisdom-based marketing communications in Sana Daja Village serve not only as a business strategy but also as a means of cultural preservation and strengthening social relationships between producers and consumers. This approach demonstrates that local values ​​can coexist with technological advancements and serve as a key foundation for creating sustainable competitiveness.